The transcription factor VaNAC17 from grapevine (Vitis amurensis) enhances drought tolerance by modulating jasmonic acid biosynthesis in transgenic Arabidopsis - Su, Lingye; Fang, Linchuan; Zhu, Zhenfei; Zhang, Langlang; Sun, Xiaoming; Wang, Yi; Wang, Qingfeng; Li, Shaohua; Xin, Haiping (Plant cell reports, 2020)
Key message Expression of VaNAC17 improved drought tolerance in transgenic Arabidopsis by upregulating stress-responsive genes, modulating JA biosynthesis, and enhancing ROS scavenging. Water deficit severely affects the growth and development of plants such as grapevine ( Vitis spp.). Members of the NAC ( N AM, A TAF1/2, and C UC2) transcription factor (TF) family participate in drought-stress-induced signal transduction in plants, but little is known about the roles of NAC genes in drought tolerance in grapevine. Here, we explored the role of VaNAC17 in Vitis amurensis , a cold-hardy, drought-tolerant species of grapevine. VaNAC17 was strongly induced in grapevine by drought, exogenous abscisic acid (ABA), and methyl jasmonate (MeJA). A transient expression assay in yeast indicated that VaNAC17 functions as a transcriptional activator. Notably, heterologous expression of VaNAC17 in Arabidopsis thaliana enhanced drought tolerance. VaNAC17 -expressing Arabidopsis plants showed decreased reactive oxygen species (ROS) accumulation compared to wild-type plants under drought conditions. RNA-seq analysis indicated that VaNAC17 expression increased the transcription of downstream stress-responsive genes after 5 days of drought treatment, especially genes involved in jasmonic acid (JA) biosynthesis (such as LOX3 , AOC1 and OPR3 ) and signaling (such as MYC2 , JAZ1 , VSP1 and CORI3 ) pathways. Endogenous JA levels increased in VaNAC17 -OE plants under drought stress. Taken together, these results indicate that VaNAC17 plays a positive role in drought tolerance by modulating endogenous JA biosynthesis and ROS scavenging.